Characterization of Thermophilic Lignocellulolytic Microorganisms in Composting - López, María J.; Jurado, Macarena M.; López-González, Juan A.; Estrella-González, María J.; Martínez-Gallardo, María R.; Toribio, Ana; Suárez-Estrella, Francisca (Frontiers in Microbiology, 2021)
Composting involves the selection of a microbiota capable of resisting the high temperatures generated during the process and degrading the lignocellulose. A deep understanding of the thermophilic microbial community involved in such biotransformation is valuable to improve composting efficiency and to provide thermostable biomass-degrading enzymes for biorefinery. This study investigated the lignocellulose-degrading thermophilic microbial culturome at all the stages of plant waste composting, focusing on the dynamics, enzymes, and thermotolerance of each member of such community. The results revealed that 58% holocellulose (cellulose plus hemicellulose) and 7% lignin was degraded at the end of composting. The whole fungal thermophilic population exhibited lignocellulose-degrading activity, while roughly 8-10% of thermophilic bacteria had this trait, though exclusively for hemicellulose degradation (xylan-degrading). Because of the prevalence of both groups, their enzymatic activity, and the wide spectrum of thermotolerance, they play a key role in the breakdown of hemicellulose during the entire process, while the degradation of cellulose and lignin is restricted to the activity of a few thermophilic fungi that persists at the end of the process. The xylanolytic bacterial isolates (159 strains) included mostly members of Firmicutes (96%) besides a few representatives of Actinobacteria (2%), and Proteobacteria (2%). The most prevalent species were Bacillus licheniformis and Aeribacillus pallidus. Thermophilic fungi (27 strains) comprised only four species, including Thermomyces lanuginosus, Talaromyces thermophilus, Aspergillus fumigatus, and Gibellulopsis nigrescens, of whom A. fumigatus and T. lanuginosus dominated. Several strains of the same species evolved distinctly at the stages of composting showing phenotypes with different thermotolerance and new enzyme expression, even not previously described for the species, as a response to the changing composting environment. Strains of Bacillus thermoamylovorans, Geobacillus thermodenitrificans, T. lanuginosus, and A. fumigatus exhibiting considerable enzyme activities were selected as potential candidates for the production of thermozymes. This study lays a foundation to further investigate the mechanisms of adaptation and acquisition of new traits among thermophilic lignocellulolytic microorganisms during composting as well as their potential utility in biotechnological processing.